Village based information display of health facility data and public awareness of Dengue Hemorrhagic Fever: a lesson from Mlati Primary Health Care Center of Yogyakarta Province - Setyaningrum, Veronika Evita; Purwandari, Ari; Sudiyo, Sudiyo; Hasanbasri, Mubasysyir (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Public health agencies concern about the disease contraction processes at the population level. Early detection and prompt treatment can be made to prevent transmission in the earliest stage. Understanding that their areas are endemic to DHF and the fact that cases continue to occur from year to year, community and public health stakeholders have a reduced motivation to take actions to have precaution to dengue. The village community will not be aware of the problems until patients from their areas visit health facility. The goal of this paper is to illustrate health center initiative to raise DHF precaution through village based spatial data display of dengue for the villagers attention in raising agenda in the management of dengue hemorrhagic fever at the level where they live. The paper points out the success story of the team of health facility manager, active public health program managers, an information technology literate administrators, and participation of local and private health workers asking DHF suspects to have their blood test in the health center. Supporting staff with health informatics training background has been able to work together with laboratory workers. The laboratory workers input the computer application that translate patient thrombocyte count data into village based geographic-spatial display. These data provide quick evidence about what is happening in the population. Puskesmas manager has the MPH training with population health perspective and the moral of public health problem solving. By having this data, she could make the health promotion actions at the population level. This paper shows the ability of health center manager to link health facility data and the population level evidence for public health action. The data can be used to trigger community be aware of DHF and to raise agenda in the prevention of local diseases. This is an easy and feasible things to do. Primary care and public health are under the common responsibility of the puskesmas managers. It is clear that data of health facility serve as the warning system of disease contracting process at the population level and the promotion of simple evidence to push community to get involved in prevention activities.